Neuroactive steroids in the programming of neurodevelopment: implications of maternal obesity - Zamora-Sánchez, Carmen J.; González-Orozco, Juan Carlos; Mendoza-Ortega, Jonatan; Villegas-Soto, Mariana L.; Camacho-Arroyo, Ignacio; Estrada-Gutierrez, Guadalupe (Frontiers in Endocrinology, 2025)
Neuroactive steroids synthesized within the maternal-placental-fetal unit play a crucial role in fetal neurodevelopment by regulating cell proliferation, migration, and myelination, neurogenesis, gliogenesis, and synaptogenesis, ultimately shaping brain maturation. Dysregulation of neuroactive steroid metabolism, receptor signaling, and downstream pathways has been linked to neurodevelopmental and mood disorders. Maternal overweight and obesity, increasingly prevalent worldwide, induce profound metabolic and hormonal adaptations that may interfere with neuroactive steroid synthesis and function. These disturbances are associated with a higher risk of autism spectrum disorder, attention deficit hyperactivity disorder, and cognitive impairments in offspring, frequently with sex-specific effects. Despite these observations, the impact of obesity on neuroactive steroid levels and their regulatory roles during pregnancy remains poorly understood. This review synthesizes preclinical and clinical evidence on the biosynthesis, mechanisms of action, and neurodevelopmental effects of neuroactive steroids during the critical window of fetal programming. Furthermore, it highlights a current knowledge on how maternal overweight and obesity alter neuroactive steroid metabolism within the maternal–placental–fetal unit and explores their potential contribution to adverse neurodevelopmental outcomes. Addressing these knowledge gaps may uncover novel biomarkers and therapeutic targets to improve neurodevelopmental trajectories in populations increasingly exposed to maternal metabolic comorbidities.